Optimizing graphene-silver embedded phase change composite synthesis using design of experiments - Paul, John; Pandey, A. K.; K., Kadirgama; Mahendran, Samykano; Jacob, Jeeja; Selvaraj, Jeyraj; Saidur, R. (Elsevier Ltd, 2024)
The paradigm shift from fossil fuels to renewable ones is at stake with the underdeveloped energy storage technology. However, Phase Change Materials (PCMs) are congruent with batteries but possess degraded thermophysical properties, which can be tuned by dispersing nanofillers. Numerous trials are needed to find the optimum responses for maximal thermophysical properties. This research aims to apply statistical methods for hybrid nanocomposite synthesis to deliver maximal favourable thermophysical properties. Response Surface Methodology with a central composite design was sourced to generate optimal input response conditions for maximal thermal conductivity. The present work also focuses on the synthesis and thermophysical characterization of nanocomposite with nanofillers (graphene: silver) at optimum input response. The maximal thermal conductivity value for the optimum input response of nanofiller and surfactant concentration was 0.412 W/mK, 0.310 %, and 0.313 %, respectively. Statistical parameters (f-values, predicted R2, observed R2, adjusted R2) were used to validate the experimentally developed Response Surface Methodology (RSM) model. The reliability of the predicted model was proved as there was little distinction between simulation data and validation experiments. The induction of statistical methods will significantly reduce the experimental trials and deliver insight into major input parameters and their effects on responses. Moreover, the macro-packed nano phase change composite reduced the surface temperature by 7 °C. The thermophysical characterization and experimental results validate the usage of NPCCs as a thermal interface material for building thermal management applications.